Accountability and Social Action in Health: A Case Study on Solid Waste Management in three Local Authority Areas of Zimbabwe - Training and Research Suport Cenre (TARSC); Civic Forum on Housing (CFH) (My University, 2013)
This case study documents the experiences of community members, community based researchers and two institutions viz. TARSC and CFH in sustainable management of soild waste and strengthening the accountability of private sector and local authorities in integrated solid waste management. Besides, it highlights responsiveness of authorities vis. a. vis. social action and accountability in solid waste management and strengthening Social Awareness and Action in Health.
Report based on a participatory research intervention by Training and Research Support Centre (TARSC) and Civil Forum on Housing (CFH).
Keywords: Solid Waste Management